(untitled) (TEST Ticontre. Theory Text Translation, 2014)
Le passage d’un original (texte-stimulus) à un texte destinataire ne se produit comme “transport” que dans des versions dites de service ou des traductions techniques ; en littérature (et spécifiquement en poésie), le traducteur se meut dans l’espace d’un sens naissant, entre son et signifié, un espace d’entrelangue où s’informe et se fixe en signes l’intention même (ou la tension) de l’expression, à partir de la matière ou substance des contenus fournis par l’original. The transition from an original (stimulus text) to a target text evolves as “transport” only in word-for-word or technical translation. In literature, and even more so in poetry, the translator moves across the space of a dawning sense which extends from the sound to the signified. This is the space of in-between languages where the intention (or tension) of the ex- pression is in-formed into signs generating from the matter or substance of the contents provided by the original text.